PEMANFAATAN ETNOBOTANI JENIS-JENIS TANAMAN OBAT DI DUSUN WAINUSALAUT DESA SULI KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH DAN IMPLIKASINYA SEBAGAI BAHAN AJAR MATA KULIAH BOTANI TUMBUHAN TINGGI - Ruslia Pulu; Alwi Smith (Program Studi Pendidikan Biologi FKIP Unpatti, 2018)
Background: Medicinal plants are all plants that can be used as medicine, ranging from those seen by the eye to those that appear under a microscope. Medicinal plants are all types of medicinal plants that are known or believed to have medicinal properties, which are grouped into traditional medicinal plants. The purpose of this study was to determine the types of medicinal plants used by the people of Wainusalaut Village as traditional medicine. Method: This type of research is qualitative with survey and interview techniques. Results: Research shows that 24 types of medicinal plants have been known to have been cultivated by the people of Wainusalaut Village and which have the potential as a drug as many as 18 species of plants that enter into 20 families. The part that is often used by the villagers of Wainusalaut is stems, roots, leaves and fruit. Conclusion: There are 24 types of medicinal plants that have been cultivated by the people of Wainusalaut Village